Understanding the Drivers of Business Formation Process in Latin America: An Integrated Model Applied to the Analysis of Alumni’s Ventures from an Ecuadorian University - Roberto Vallejo-Imbaquingo; Andrés Robalino-López (Systems)
Recognizing the factors that influence business formation in developing contexts is critical for promoting economic growth. This study examines the drivers of entrepreneurship among university alumni in Ecuador, addressing gaps in the literature regarding the roles of individual, organizational, and institutional factors in business creation. Drawing on established theories such as the Theory of Planned Behavior and Resource-Based Theory, a multilevel causal model was developed and tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 550 alumni through a structured questionnaire, complemented by semi-structured interviews. The model integrates micro-level (entrepreneurial attitudes and funding experience), meso-level (entrepreneurial knowledge acquired from working experience), and macro-level determinants (opportunity cost). Results indicate that while individual traits play a role, organizational knowledge and institutional context have more pronounced impacts on entrepreneurial actions. In particular, opportunity costs have a negative impact on the business formation process, reflecting the challenges of entrepreneurship in unfavorable environments. The findings highlight the importance of fostering entrepreneurial ecosystems within universities, emphasizing education and support mechanisms tailored to overcoming institutional barriers. This study contributes to the understanding of entrepreneurship in Latin America, offering insights for policymakers and academic institutions aiming to enhance entrepreneurial activity and economic development.